Bifactor analysis and construct validity of the five facet mindfulness questionnaire (FFMQ) in non-clinical Spanish samples - Aguado, Jaume; Luciano, Juan V.; Cebolla, Ausias; Serrano-Blanco, Antoni; Soler, Joaquim; García-Campayo, Javier (Frontiers in Psychology, 2015)
The objective of the present study was to examine the dimensionality, reliability, and construct validity of the Five Facet Mindfulness Questionnaire (FFMQ) in three Spanish samples using structural equation modelling (SEM). Pooling the FFMQ data from 3 Spanish samples (n= 1191), we estimated the fit of two competing models (correlated five-factor vs. bifactor) via confirmatory factor analysis. The factorial invariance of the best fitting model across meditative practice was also addressed. The pattern of relationships between the FFMQ latent dimensions and anxiety, depression, and distress was analysed using SEM. FFMQ reliability was examined by computing the omega and omega hierarchical coefficients. The bifactor model, which accounted for the covariance among FFMQ items with regard to one general factor (mindfulness) and five orthogonal factors (observing, describing, acting with awareness, non-judgment, and non-reactivity), fit the FFMQ structure better than the correlated five-factor model. The relationships between the latent variables and their manifest indicators were not invariant across the meditative experience. Observing items had significant loadings on the general mindfulness factor, but only in the meditator sub-sample. The SEM analysis revealed significant links between mindfulness and symptoms of depression and stress. When the general factor was partialled out, the acting with awareness facet did not show adequate reliability. The FFMQ shows a robust bifactor structure among Spanish individuals. Nevertheless, the Observing subscale does not seem to be adequate for assessing mindfulness in individuals without meditative experience.